Rancang Bangun Alat Pengamanan Kotak Amal Menggunakan Sensor Sidik Jari dan SMS Gateway Berbasis Mikrokontroler - Thomas Yudi Irawan; Yoga Listi Prambodo; Iskandar Zulkarnain (Sistem Komputer & Teknologi Intelegensi Artifisial (SIKOMTIA), 2022)
Charity boxes provided in many public places today still use locks such as master locks or padlocks. The rampant cases of theft of charity boxes occur repeatedly because charity boxes are easily broken into and even transported by thieves. The absence of a double security system is an obstacle for charity box managers. Realizing the design concept of a double security system for charity boxes using several electronic components such as fingerprint sensors and methods of sending notifications will minimize the occurrence of the crime of theft or burglary of charity boxes. The security device design architecture is made using the notification method in the form of notifications via short messages using a communication device, namely the SIM800L serial module as a transmission medium for sending short message text data if irregularities are found in the charity box. This charity box security system uses an authorization system for managers who are entitled to be registered with the device in the form of a cellular number. The microcontroller control board plays an important role in processing various instructions so as to produce output information on the screen that is installed in the charity box to display access information when the device is working. Another feature of this tool is that it is equipped with a buzzer component as a warning sign in the form of a sound if an activity process is not recognized it will ring loudly according to the conditions. A security system like this will provide a solution and increase security in the storage of charity boxes so managers can feel comfortable.